Error Analysis on Descriptive Text of Non-English Teachers at Al Islam Junior High School Kartasura - Umi Sholehah; Ike Anisa (Surakarta English and Literature Journal, 2019)
This article is based on the research of language error in English descriptive text by non-English teachers at Al Islam Junior High School Kartasura. The subject of this research is non-English teachers at Al Islam Junior High School Kartasura which consists of eleven teachers. This research aims to analyze English writing ability of the Non-English teachers, especially in descriptive paragraph. The method of the study in this research is descriptive qualitative with intralingual method in analyzing it. Based on the data finding, the researcher tries to make groups the data based on the errors. There are phonological errors done by 9 teachers, morphological errors done by 2 teachers, and structural errors done by 9 teachers.